2014
DOI: 10.1007/s40261-014-0224-z
|View full text |Cite|
|
Sign up to set email alerts
|

Cost Effectiveness of Apixaban Versus Aspirin for Stroke Prevention in Patients with Non-Valvular Atrial Fibrillation in Belgium

Abstract: Apixaban is a cost-effective alternative to aspirin for patients with AF in Belgium who decline or cannot tolerate VKA treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…1, included in the model were NVAF, ischaemic stroke and haemorrhagic strokes (mild, moderate, severe and fatal), intracranial haemorrhage (ICH) other than haemorrhagic strokes (referred to as other ICH), systemic embolism, myocardial infarction (MI), other major bleeds (non-ICH major bleeds), clinically relevant non-major bleeding and NVAF with subsequent aspirin treatment or death. Details surrounding the model transitions, methodology around obtaining clinical inputs and assumptions have been previously described in detail [15,23,29], however, they are summarised in Tables 1 and 2 for completion.…”
Section: Model Designmentioning
confidence: 99%
“…1, included in the model were NVAF, ischaemic stroke and haemorrhagic strokes (mild, moderate, severe and fatal), intracranial haemorrhage (ICH) other than haemorrhagic strokes (referred to as other ICH), systemic embolism, myocardial infarction (MI), other major bleeds (non-ICH major bleeds), clinically relevant non-major bleeding and NVAF with subsequent aspirin treatment or death. Details surrounding the model transitions, methodology around obtaining clinical inputs and assumptions have been previously described in detail [15,23,29], however, they are summarised in Tables 1 and 2 for completion.…”
Section: Model Designmentioning
confidence: 99%
“…The same assumption was applied in other prior studies. [17][18][19] In addition, results from univariate sensitivity analysis, varying utility for each clinical event by its' 95% confidence intervals, demonstrated that the ICERs were altered by only less than 4%.…”
Section: Discussionmentioning
confidence: 99%
“…To fit the 3-month cycle length of the model, all included transition probabilities were scaled to 3 months, assuming a constant rate in accordance with the methods described by Briggs et al [29]. Rates were converted into probabilities under the assumption of a constant rate model [31,32]. Input parameters limited within the range of 0-1, as for probabilities, were assumed to be outcomes of betadistributed derivates [30], whereas gamma distributions were assumed for non-negative parameters as rates.…”
Section: Transition Probabilitiesmentioning
confidence: 99%